Juglibub Corp - Tan, Joseph Jericho (Animo Repository, 2021)
Over the years, the plastic waste or pollution has been an ongoing issue worldwide. Several plastic wastes are not being recycled and are just being thrown away. An example of which are the plastic bottles from brands such as Absolute, Pepsi, Coca-Cola, and the likes. Once the consumer finishes drinking their beverage, the consumer leaves a trace of plastic wastes. As such, Juglibub Corporation aims to have a positive contribution in the environment due to this issue. Juglibub Corporation introduced their collapsible water bottle in the market. Collapsible water bottles are convenient for the consumers as it can change sizes and liquid capacity depending on the consumers’ preference. Moreover, due to the small size factor of the water bottle, it can easily be placed in one’s bag. The collapsible water bottle is of quality and durable, which is a must for the consumers to last a long time. Juglibub Corporation also introduced their very own Aloe Vera Disinfectant Spray which is currently an essential due to the current pandemic. The Aloe Vera Disinfectant Spray is packaged in a Card Type Spray Holder which can easily fit the pockets of a pants. The team saw this as an opportunity to somewhat lessen the daily COVID-19 cases. The collapsible water bottle addresses the plastic waste issues and hopefully, Juglibub Corporation was able to lessen the plastic wastes in the Philippines. Regarding the Aloe Vera Disinfectant Spray, the team saw this as an opportunity to somewhat lessen the daily COVID-19 cases. With Juglibub Corp.’s products, the team was able to have a positive contribution in the environment with their reusable collapsible water bottle and the Aloe Vera Disinfectant Spray.